2013
DOI: 10.1126/science.1230624
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 Prevents Resection of DNA Breaks and Promotes Immunoglobulin Class Switching

Abstract: DNA double-strand breaks (DSBs) represent a threat to the genome because they can lead to loss of genetic information and chromosome rearrangements. The DNA repair protein p53 binding protein 1 (53BP1) protects the genome by limiting nucleolytic processing of DSBs by a mechanism that requires its phosphorylation, but whether it does so directly is not known. Here we identify Rapl-interacting factor 1 (Rif1) as an Ataxia-Telangiectasia Mutated (ATM) phosphorylation-dependent interactor of 53BP1, and show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
375
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(395 citation statements)
references
References 48 publications
14
375
1
Order By: Relevance
“…Similarly, elevated levels of Rif1 were found in breast cancer and teratocarcinomas (Wang et al ., 2009; Li et al ., 2015). Since mammalian Rif1 participates in suppressing the HDR repair pathway in the G1 phase (Chapman et al ., 2013; Di Virgilio et al ., 2013; Escribano‐Díaz et al ., 2013; Zimmermann et al ., 2013), it was suggested that too much Rif1 drives illicit and error‐prone DSB repair, which alters the genome. However, our study shows that Rif1 can drive genomic instability in the absence of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, elevated levels of Rif1 were found in breast cancer and teratocarcinomas (Wang et al ., 2009; Li et al ., 2015). Since mammalian Rif1 participates in suppressing the HDR repair pathway in the G1 phase (Chapman et al ., 2013; Di Virgilio et al ., 2013; Escribano‐Díaz et al ., 2013; Zimmermann et al ., 2013), it was suggested that too much Rif1 drives illicit and error‐prone DSB repair, which alters the genome. However, our study shows that Rif1 can drive genomic instability in the absence of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors are, for example, Ku70/ 80, 53BP1, and Rif1 (39)(40)(41)(42). Many classical HR factors are also implicated to be required for CSR, for example the Mre11, Rad50, and Nbs1 complex, RPA, and possibly CtIP (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Originally discovered for its role at yeast telomeres and later identified as important for controlling DNA replication, Rif1 is now known to mediate various additional chromosome stability functions, including DNA break repair pathway choice (Chapman et al 2013;Di Virgilio et al 2013;Escribano-Diaz et al 2013) and down-regulation of checkpoint activity close to telomeres (Xue et al 2011;Ribeyre and Shore 2012). All of these control mech-anisms could potentially involve regulated dephosphorylation of specific proteins.…”
Section: Evolutionary Conservation Of Pp1 Interaction Motifs In Rif1mentioning
confidence: 99%
“…It has since been demonstrated that S. cerevisiae Rif1 suppresses activation of the DNA damage checkpoint near telomeres (Xue et al 2011;Ribeyre and Shore 2012) and affects telomere replication time (Lian et al 2011). The presence of Rif1 is evolutionarily conserved, but in other eukaryotes, Rif1 has been shown to play nontelomeric roles, such as directing the pathways used in DNA double-strand break repair and DNA recombination (Chapman et al 2013;Di Virgilio et al 2013;EscribanoDiaz et al 2013). Recent studies have implicated the fission yeast (Schizosaccharomyces pombe) and mammalian Rif1 proteins in the regulation of DNA replication genome-wide.…”
mentioning
confidence: 99%